Konseling individu melalui metafora terapeutik video puisi untuk menstabilkan emosi akibat perceraian orangtua pada Siswa SMAN 6 Pontianak - Halida, Halida; Putri, Amallia (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This research aims to determine the effectiveness of individual counseling using the therapeutic metaphor of poetry videos to increase the meaningfulness of life due to parental divorce in students. The specific target to be achieved in this research is to dig deeper into the workings of individual counseling services with poetry videos through appropriate individual counseling steps so that their effectiveness can be seen. To measure the increased meaning of life due to parental divorce in students, emotional stability instruments were used both before and after treatment. This research uses an experimental design with a pretest posttest group design. The instrument given to the sample was an instrument developed by the author himself. In this design there is one group selected by purposive sampling. Based on data analysis, the average pretest value was 101.25 and after being treated, the posttest value was 57.8 with a Wilcoxon signed-rank test Z value of 118.25, with a p value of 0.006, which means the p value is smaller than 0.05. So it can be concluded that Ha was accepted and Ho was rejected, which means individual counseling through the therapeutic metaphor of poetry videos is effective for stabilizing emotions due to parental divorce.